PERANCANGAN SISTEM INFORMASI PENGELOLAAN HASIL PENJUALAN TIKET WISATA PANYAWEUYAN ARGAPURA - Nuraisah, Aas; Budiman (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2025)
In the modern era, technology plays an important role in facilitating human activities. Innovations in information management through the internet are closely related to rapid technological developments and have an impact on various sectors, including tourism. According to Law No. 10 of 2009, tourism covers all activities in the tourism industry that involve travelers and local communities. One of them is Panyaweuyan Argapura tourism, Majalengka Regency. In an effort to improve tourism services, researchers designed an information system application to facilitate the management of ticket sales digitally. This system was built using the PHP programming language and the Waterfall method. This method was chosen because it has structured stages that facilitate the system development process. Testing was carried out using the blackbox and whitebox methods to ensure that the features ran according to requirements and that the program logic functioned optimally. Testing results showed that the application functions well and is ready for use by tourism managers. “PAMPA” Panyaweuyan Tourism Management is an application designed to facilitate the administrative management of ticket sales at the Panyaweuyan tourist destination. This application aims to provide an efficient solution for tourism managers in recording, monitoring, and analyzing ticket sales results. It is hoped that this application will become a solution to these problems.